2021
DOI: 10.1002/fam.3013
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the suppression characteristic of deoxidization gel foam on coal spontaneous combustion

Abstract: Summary Mine fire caused by coal spontaneous combustion is one of the main safety problems in mining. For the purpose of developing a more effective inhibitor to suppress the coal spontaneous combustion, a compound deoxidization gel foam inhibitor was proposed by combining sodium dithionite deoxidizer with gel foam. An experimental platform was self‐built to evaluate the suppression characteristic of deoxidization gel foam. Experimental results showed that the deoxidization gel foam reduced the oxygen concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…It prevented the further oxidation of the coal structural group −OO and thus terminated the chain reaction of free radicals in the coal. Lu et al [67] incorporated sodium dithionite, calcium hydroxide, and activated carbon in a gel foam for a composite deoxygenation gel foam. It has an inhibitory effect on coal oxygen adsorption by blocking the coal radical chain reaction by reducing the alkyl, hydroxyl, and carbonyl groups of coal.…”
Section: Silicate Gel Foammentioning
confidence: 99%
See 1 more Smart Citation
“…It prevented the further oxidation of the coal structural group −OO and thus terminated the chain reaction of free radicals in the coal. Lu et al [67] incorporated sodium dithionite, calcium hydroxide, and activated carbon in a gel foam for a composite deoxygenation gel foam. It has an inhibitory effect on coal oxygen adsorption by blocking the coal radical chain reaction by reducing the alkyl, hydroxyl, and carbonyl groups of coal.…”
Section: Silicate Gel Foammentioning
confidence: 99%
“…The results showed that the blocking effect of each particle size of the coal sample by gel foam was in the order of large particle size > medium particle size > small particle size. Lu et al [107] used a coal self-ignition signature gas determination experimental system and a simultaneous analyzer to test the coal warming rate, the development pattern of signature gas, and the characteristic temperature and thermal effect of coal during pyrolysis of coal samples treated with gel foam, respectively. It was found that the hindering performance of gel foam was better compared with waterbased foam and slurry.…”
Section: Inhibition Propertiesmentioning
confidence: 99%